A profile of acute poisonings: A retrospective study - Thalappillil Mathew Celine (Journal of the Scientific Society, 2015)
Background and Objective: Intentional self-poisoning is a major problem in developing countries. Thus, the main objective of this study was to characterize the poisoning cases and related mortality among patients admitted with poisoning in a tertiary care hospital during the period from April 1, 2005 to March 31, 2010. Materials and Methods: A retrospective study conducted on hospitalized patients admitted with poisoning. Data were collected from the registers kept in the medical records department, which follows the guidelines of International Classification of Diseases-10 coding. Results: Of 2018 cases, 1178 (56.6%) were males and 903 (43.4%) females. Most of the cases were in the age of 26-45 years. Of the total cases, 412 (19.8%) admitted with organophosphorus and carbamate insecticides poisoning. Among them, males 264 (22.4%) were more than females 148 (16.4%). Case fatality rate due to poisoning was 7.8% (162 deaths). Of the total deaths, 66.0% were occurred among males and 34% among females. Of the deaths, 35.2% deaths were due to organophosphorus and carbamate insecticides poisoning. Case fatality due to organophosphorus and carbamate insecticides poisoning was 13.8%. Conclusion: In the present study organophosphorus and carbamate insecticides poisoning cases and its mortality were high. The easy availability of dangerous poisons from the shops should be restricted for controlling these types of poisonous deaths.